The use of social work services in criminal matters : an exploratory study of East London attorneys - McCoy, Lee (Rhodes University, Faculty of Humanities, Department of Social Work, 2003)
This study explored the use of social work services by East London attorneys in criminal law matters. Semi-structured interviews were conducted and the data was saturated after 10 such interviews. In exploring the use of social work services, the study also considered the challenges and constraints experienced by lawyers in their use of expert witnesses from the Humanities generally; discussed the expectations lawyers have of expert witnesses and the presentencing reports they write and described the perceived impact of social work services on the presentation of cases in criminal matters. The focus on social work was aimed at exploring ways of increasing the use of social work as the profession of choice when attorneys call on expert witnesses. The literature revIew focussed on the individualisation of sentences, the general principles of punishment, finding an appropriate sentence, the so-called Triad of Zinn, the role of the social worker in criminal justice, the role of the legal social worker, the report, courtroom skills and the relationship between social work values and the law. Using purposive sampling of all legal firms in East London doing criminal work, ten attorneys were asked to participate in the study. A semi-structured interview based on a schedule of questions was used. The interviews were recorded and transcribed. The transcripts were analysed thematically. After ten interviews no new data was being generated and the topic was considered saturated. Further research is needed to build on the themes that emerged. The study argues that there is a place for social work services in criminal matters. It also, however, revealed that some of the respondents had had negative experiences when dealing with social workers. There were also positive responses and a commitment to establishing a more co-operative relationship between law and social work. Based on the research findings, the most important recommendation was to develop communication between the two professions and to provide inter-disciplinary training so as to promote an understanding of the roles and expectations of all involved in the criminal law process.
Keywords: Social workers -- Legal status, laws, etc. -- South Africa -- East London; Social service -- South Africa -- East London; Lawyers -- South Africa -- Attitudes